HIV prevention transformed: the new prevention research agenda - Padian, Nancy S. (2011)
We have entered a new era in HIV prevention whereby priorities have expanded from biomedical discovery to include implementation, effectiveness, and the effect of combination prevention at the population level. However, gaps in knowledge and implementation challenges remain. In this Review we analyse trends in the rapidly changing landscape of HIV prevention, and chart a new path for HIV prevention research that focuses on the implementation of effective and efficient combination prevention strategies to turn the tide on the HIV pandemic.